EKSPRESI CAHAYA PADA GALERI BAGI ANAK DOWN SINDROM - I Made Wahyudi Gelgel; Himaladin Himaladin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Down syndrome is a disorder that occurs in mental retardation caused by chromosomal abnormalities on number 21. Mental retardation becomes a significant problem, especially in developing countries like Indonesia. Children with down syndrome have limitations in social, cognitive, and physical development. The challenges in the delayed development of children with down syndrome require an environment designed to cater to their needs. Despite their limitations, children with down syndrome have unique abilities, such as being visual learners, imitating movements, and being highly interested in light, which are essential elements in design. Architectural empathy has an impact on children with down syndrome by understanding their needs through the empathetic process, allowing designers to comprehend their daily lives and create spaces that fulfill those needs. Expressing emotions can be difficult for children with down syndrome, even though it is a crucial way for them to communicate. Providing spaces for creative expression, such as painting, singing, and dancing, becomes essential in accommodating their expressive needs. Therefore, it is proposed to create an exession gallery with appropriate lighting to facilitate the expressive needs of children with down syndrome, along with necessary therapy facilities and consultation services. Keywords: architecture empathy; down syndrome children; needs of children with down syndrome Abstrak Down syndrome adalah kelainan yang terjadi pada retardasi mental disebabkan oleh kelainan kromosom pada no. 21. Retardasi mental menjadi masalah dengan implikasi yang besar terutama pada negara berkembang seperti Indonesia, Anak-anak dengan kondisi down syndrome memiliki keterbatasan masalah dalam perkembangan sosial, kognitif, dan fisik. Masalah dalam keterlambatan perkembangan anak down syndrome membutuhkan perancangan lingkungan yang memperhatikan kebutuhan mereka. Dibalik keterbatasan yang mereka miliki, anak down syndrome tetap mempunyai keistimewaan yaitu menjadi visual learner, peniru gerakan, dan sebagian besar tertarik terhadap cahaya, tiga keistimewaan ini menjadikan elemen penting dalam desain. Empati arsitektur memberikan dampak kepada anak down syndrome, melalui proses empati, pengalaman dari kebutuhan mereka, sehingga akan mengetahui semua keseharian anak down syndrome sehingga akan tercipta apa dari kebutuhan mereka. Anak down syndrome juga memiliki kesulitan dalam berekspresi, padahal ini adalah cara anak untuk mengungkapkan emosinya, dengan berekspresi melakukan aktivitas dan menghasilkan sebuah karya menjadi salah satu untuk mewadahinya, seperti melukis, menyanyi, dan menari, sehingga diusulkan galeri ekspresi dengan cahaya yang bisa mewadahi kebutuhan ekspresi anak down syndrome dan kebutuhan kelengkapan fasilitas terapi serta fasilitas untuk konsultasi.